Prevalence of anemia and its associated factors among geriatric patients admitted to Hospital Pakar Universiti Sains Malaysia, Kelantan, from january 2023 to june 2023 - Ahamed, Esba (Universiti Sains Malaysia, 2025)
Anemia is a common health condition characterized by a reduction in the number of red blood cells (RBCs), leading to an insufficient ability of the body to transport oxygen effectively. Anaemia is more prevalent in the geriatric population and is frequently disregarded as a factor in older adults' illnesses. The geriatric populations of many developing countries suffer significantly from anemia, with Southeast Asia and Africa having the highest prevalences. This study aimed to investigate the prevalence of anemia and its associated factors among geriatric patients (age ≥ 65 years) admitted to Hospital Pakar USM. A cross-sectional, retrospective study involving 131 patients 65 or older. Laboratory results and sociodemographic information were documented using a validated proforma format. SPSS was used to analyze the data. Most of the anemic patients were 65-69 years (31.0%), and most were male (60%). Most of the patients (74.0%) had normocytic anemia. A significant association was found between the severity of anemia and malignancy (p=0.041), gastrointestinal bleeding (p=0.050), and chronic illness (p<0.001). Anaemia was frequently diagnosed in the studied geriatric population. The most frequent cause of anemia in the geriatric population was anemia of chronic illness. Future geriatric research might examine how anemia affects functional abilities, quality of life, and recovery from illness